1996
DOI: 10.1007/bf02239045
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of heterotrophic nanoflagellates and their importance as the bacterial consumer in a eutrophic coastal seawater

Abstract: Seasonal and vertical changes in abundances of bacteria and heterotrophic nanoflagellates (HNF), and HNF grazing on bacteria were investigated in a small eutrophic inlet of Uranouchi-Wan throughout the years. Bacterial densities in the surface water ranged from 1.2 to 11 (average 4.3) × 10 6 cells ml -1 with a couple of maxima following the algal blooming. Densities of HNF ranged from 0.54 to 73 (average 16.4) × 10 3 cells ml -1 in the surface, and showed almost similar fluctuation pattern to that of bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…We emphasize, however, that at present there is no standard method to estimate the activities in sediment. Researchers for instance have measured the fluxes of oxygen and carbon dioxide 14) , the rates of nucleic acid synthesis 35,47) , and the extracellular hydrolytic activities 28,40) , to evaluate the heterotrophic processes in the sediment. Therefore, any comparisons with results from studies using other methods or model substrates for instance should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasize, however, that at present there is no standard method to estimate the activities in sediment. Researchers for instance have measured the fluxes of oxygen and carbon dioxide 14) , the rates of nucleic acid synthesis 35,47) , and the extracellular hydrolytic activities 28,40) , to evaluate the heterotrophic processes in the sediment. Therefore, any comparisons with results from studies using other methods or model substrates for instance should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…A description of the study site can be found in earlier publications 14,15,37) . In brief, the site is a semi-enclosed shallow water (depth~16-17 m) coastal ecosystem which witnesses only limited water exchange 15) , and experiences pronounced density stratification 14,37) during an annual cycle. Furthermore, the inlet contains a large number of fish rearing cages from which a considerable amount of nutrients is discharged leading to eutrophication of the inlet.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…1). The description of the site can teristically use high protein diets (McCaig et al 1999), be found elsewhere (Fukami et al 1991b(Fukami et al , 1996. In Hence, it is important to quantify their extracellular hyshort, near and around the sampling station, intensive drolysis in the recipient ecosystems, and also to know cage culture of yellow tail and red sea bream is widely the main environmental factors which regulate their practiced.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, it has even directly affected the farming by causing mass mortalities of cultivated animals (Johnsen et al 1993). 'Corresponding author: E-mail: fukami@cc.kochi-u.ac.jp In order to ensure clean coastal environments and sus-0 Inter-Research 2000 tainable farming, these allochthonous organic materihave also been reported (Fukami et al 1996). In the als must be decomposed and utilized by the microflora present paper, we describe fluctuations in the APA in or recycled within the recipient ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the last two decades, a new carbon pathway termed the "microbial loop" has been proposed (Azam et al 1983) and many studies have shown its importance in material flow (e.g. Fukami et al 1996). It is supposed whether organic carbon produced by phytoplankton goes into the grazing food chain or microbial loop depends on the physiology and/or community structure of the phytoplankton (Roman et al 1988, Levasseur et al 1996.…”
Section: Introductionmentioning
confidence: 99%